Exploring challenges and coping strategies in providing care for older adults with dementia: a qualitative study conducted in China - Cheng, Yanan; Yang, Meijiazi; Ma, Sha (Frontiers in Public Health, 2025)
BackgroundThe increasing prevalence of dementias in China has imposed a substantial burden on caregivers, posing a serious threaten to their physical and mental well-being. It is imperative to explore practical measures to alleviate the stress experienced by those caregivers of older adults with dementia.MethodsA semi-structured questionnaire was adopted for conducting interviews with the participants from December 2022 to January 2023. Subsequently, the interviews were meticulously recorded and transcribed in their entirety, followed by a rigorous analysis of the resulting data and information.ResultsA total of 17 participants who provided care for older adults with dementia were interviewed across various settings including rural areas, communities, hospitals, and nursing homes in Shandong Province. These caregivers encountered challenges such as limited social interaction, significant mental strain, deteriorating physical health, financial insufficiency, and a lack of professional expertise. The current social support systems were deemed insufficient for families caring for older adults with dementia. To alleviate the burden on dementia caregivers, particularly for those with low-income status, the government needs to prioritize enhancing the coverage of the long-term healthcare system and expanding the essential medication list. Given the growing population of older adults in China and the fact that most individuals with dementia are cared for by family members, it is recommended to establish a multifaceted support system involving collaboration among government, social organizations, and volunteers within both urban and rural communities.ConclusionThe gradual expansion of coverage of long-term care insurance, the proactive inclusion of dementia treatment drugs into the essential medication list, and optimization of a diversified dementia care system ought to be a matter of significant concern.